Pelaksanaan Penerimaan Peserta Didik Baru Sistem Zonasi - Putra, Sandika; Afriantoni; Rohman, Asep; Putra, Afriantoni (El-Idare, 2024)
This study aims to describe and explain the implementation of the New Student Admission (PPDB) at SMP Negeri 50 Palembang, as well as to identify the supporting and inhibiting factors in the implementation of PPDB. The research method used is descriptive qualitative with data collection techniques through interviews, observations, and documentation. The results show that the implementation of PPDB at SMP Negeri 50 Palembang has been carried out well in terms of coordination, motivation, communication, and direction. The PPDB committee chairperson has effectively fulfilled their duties by assigning responsibilities to members, and the principal has provided effective motivation through discussions with all members. Communication among the committee members also runs smoothly, fostering good working relationships. The direction in the PPDB process, from committee formation to final evaluation, was conducted systematically. The main supporting factors in the PPDB implementation at SMP Negeri 50 Palembang are the strategic location of the school and the quality of the teaching staff, which have been well accredited. However, there are inhibiting factors related to the inadequate physical condition of the school's facilities, such as faded, moldy, and graffiti-covered walls, with no significant renovation efforts yet undertaken. This study concludes that despite some obstacles, the overall implementation of PPDB at SMP Negeri 50 Palembang has adhered to the established procedures and successfully attracted prospective students, although improvements to the school's physical condition are still needed to enhance educational quality.